A TRAVESSIA: relato de uma formação em medicina durante a pandemia de COVID-19 - Rodigheri, Vitor (Universidade Federal de São Carlos, 2025)
This Final Coursework consists of an experience report in a narrative format about the six-year journey through undergraduate medical training at the Federal University of São Carlos (UFSCar) between 2020 and 2025. The objective is to analyze the difficulties, learnings, and transformations that shaped the construction of my professional identity. The trajectory is initially marked by the impact of the COVID-19 pandemic, which imposed a distance learning model for the first two years. This phase generated frustration due to the absence of practical activities, insecurity with clinical skills, and the need to develop resilience and proactivity. The return to in-person learning from the third year onward represented a "turning point," allowing for the rediscovery of the passion for medical practice, despite the reality shock of dealing with the complexity of real patients. The fourth year was a period of consolidating confidence and maturing clinical reasoning, with the development of the concept of "longitudinal care". The internship (fifth and sixth years) is described as a "culture shock" between hospital medicine and primary care, and as the period of definitive discovery of the vocation for Internal Medicine, motivated by the intellectual challenge of complex cases. Extracurricular activities are presented as a strategic tool that evolved from online exploration to immersive internships that solidified the choice of the future specialty. It is concluded that, despite its flaws and challenges, the training was paradoxically effective in forging a resilient professional with a profound clarity about his path in medicine.
THE JOURNEY: a report of medical learning during the COVID-19 pandemic
Keywords: Formação médica; Relato de experiência; Pandemia de COVID-19; Internato médico; Identidade profissional; Medical education; COVID-19 pandemic; Medical internship; Professional identity; Experience report; CIENCIAS DA SAUDE::MEDICINA; 4. Educação de Qualidade